A practicable branch-and-bound algorithm for globally solving linear multiplicative programming. (4th March 2017) - Wang, Chun-Feng; Bai, Yan-Qin; Shen, Pei-Ping
Abstract: To globally solve linear multiplicative programming problem (LMP), this paper presents a practicable branch-and-bound method based on the framework of branch-and-bound algorithm. In this method, a new linear relaxation technique is proposed firstly. Then, the branch-and-bound algorithm is developed for solving problem LMP. The proposed algorithm is proven that it is convergent to the global minimum by means of the subsequent solutions of a series of linear programming problems. Some experiments are reported to show the feasibility and efficiency of this algorithm.